Ultraviolet B (UVB) Radiation Induces Skin Alterations, Emperipolesis and Decreases the Erythroid-to-myeloid Ratio in Rats - Verda Farida; Dion Adiriesta Dewananda; Muhammad Novrizal Abdi Sahid; Siti Isrina Oktavia Salasia (Indonesian Biomedical Journal)
BACKGROUND: Ultraviolet B (UVB) radiation is commonly known to be related to skin inflammation. The inflammation process is orchestrated by many cell types, including immune cells. Changes in bone marrow cellularity can also be an indicator of inflammation. Megakaryocytes, myeloid immune cells progenitor and erythroid progenitor cells, are at high risk of changes upon UVB irradiation. However, there are still limited study observing the change of bone marrow cell population after UVB irradiation. Therefore, this study was conducted to investigate the alteration of the skins, emperipolesis, and the change in erythroid and myeloid cell population in bone marrow after UVB irradiation.